"a_4=a_3+d=a_1+3d, a_5=a_4+d=a_1+4d"
"\\tan (a_2-a_1)=\\dfrac{\\tan a_2-\\tan a_1}{1+\\tan a_1\\tan a_2}"
"\\tan a_1\\tan a_2=\\dfrac{\\tan a_2-\\tan a_1}{\\tan(d)}-1"
"\\tan a_2\\tan a_3=\\dfrac{\\tan a_3-\\tan a_2}{\\tan(d)}-1"
"\\tan a_3\\tan a_4=\\dfrac{\\tan a_4-\\tan a_3}{\\tan(d)}-1"
"\\tan a_4\\tan a_5=\\dfrac{\\tan a_5-\\tan a_4}{\\tan(d)}-1"
"+\\tan a_3\\tan a_4+\\tan a_4\\tan a_5="
"+\\dfrac{\\tan a_4-\\tan a_3}{\\tan(d)}-1+\\dfrac{\\tan a_5-\\tan a_4}{\\tan(d)}-1"
Then
"+\\dfrac{\\tan a_4-\\tan a_3}{\\tan(d)}-1+\\dfrac{\\tan a_5-\\tan a_4}{\\tan(d)}-1=11"
"\\tan a_5-\\tan a_1=15\\tan(d)"
"\\dfrac{\\sin(a_3+2d)}{\\cos(a_3+2d)}-\\dfrac{\\sin(a_3-2d)}{\\cos(a_3-2d)}=15\\tan(d)"
"\\dfrac{\\sin(a_3+2d)\\cos(a_3-2d)-\\cos(a_3+2d)\\sin(a_3-2d)}{\\cos(a_3+2d)\\cos(a_3-2d)}="
"=15\\tan(d)"
"\\dfrac{\\sin(a_3+2d-a_3+2d)}{\\dfrac{1}{2}\\big(\\cos(4d)+\\cos(2a_3)\\big)}=15\\tan(d)"
"\\cos(4d)+\\cos(2a_3)=\\dfrac{2\\sin(4d)}{15\\tan(d)}"
"\\cos(2a_3)=\\dfrac{2\\sin(4d)}{15\\tan(d)}-\\cos(4d)"
"2\\cos^2(a_3)-1=\\dfrac{2\\sin(4d)}{15\\tan(d)}-\\cos(4d)"
"2\\cos^2(a_3)=\\dfrac{2\\sin(4d)}{15\\tan(d)}+(1-\\cos(4d))"
"2\\cos^2(a_3)=\\dfrac{2\\sin(4d)}{15\\tan(d)}+2\\sin^2(2d)"
"\\cos^2(a_3)=\\dfrac{\\sin(4d)}{15\\tan(d)}+\\sin^2(2d)"
"\\cos(d)=\\sqrt{0.6}=>\\sin(d)=\\pm\\sqrt{1-(\\sqrt{0.6})^2}=\\pm\\sqrt{0.4}"
Let "\\sin(d)=\\sqrt{0.4}." Then
"\\cos(2d)=2\\cos^2(2d)-1=2(\\sqrt{0.6})^2-1=0.2"
"\\sin(2d)=2\\sin(d)\\cos(d)=2\\sqrt{0.4}\\sqrt{0.6}=0.4\\sqrt{6}"
"\\sin(4d)=2\\sin(2d)\\cos(2d)=2(0.4\\sqrt{6})(0.2)=0.16\\sqrt{6}"
"\\sin^2(2d)=(0.4\\sqrt{6})^2=0.96"
"\\cos^2(a_3)=\\dfrac{0.16\\sqrt{6}}{15\\sqrt\\dfrac{2}{3}{}}+0.96=0.992"
Let "\\sin(d)=-\\sqrt{0.4}." Then
"\\cos(2d)=2\\cos^2(2d)-1=2(\\sqrt{0.6})^2-1=0.2"
"\\sin(2d)=2\\sin(d)\\cos(d)=-2\\sqrt{0.4}\\sqrt{0.6}=-0.4\\sqrt{6}"
"\\sin(4d)=2\\sin(2d)\\cos(2d)=-2(0.4\\sqrt{6})(0.2)=-0.16\\sqrt{6}"
"\\sin^2(2d)=(-0.4\\sqrt{6})^2=0.96"
"\\cos^2(a_3)=\\dfrac{-0.16\\sqrt{6}}{-15\\sqrt\\dfrac{2}{3}{}}+0.96=0.992"
"\\cos^2(a_3)=0.992"
Comments
Leave a comment